The Effectiveness of the Problem-Based Learning Model Assisted by Mind Mapping in Natural and Social Sciences Subjects (IPAS) - Diah Ayu Safira; Teguh Supriyanto; Trimurtini Trimurtini (Jurnal Penelitian Pendidikan IPA, 2024)
Natural and Social Sciences (IPAS) education in Indonesia has emerged and evolved through various changes in accordance with the conditions and needs of the Indonesian nation. The aim of this research is to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by Mind Mapping in Grade IV at SDN Kalibanteng Kidul 01, Semarang City, for the Social Studies subject focusing on Indonesia's rich culture. The research employs a quasi-experimental design. The study population consists of all Grade IV students from SDN Kalibanteng Kidul 01, Semarang City, for the 2023/2024 academic year, with a total of 81 students. This population is divided into an experimental class (Grade IV A) and a control class (Grade IV B). The average posttest score of the experimental class was higher than that of the control class, with the experimental class scoring 81.60 and the control class scoring 60.17. The ttable value was found to be 1.701. With this, it can be concluded that H0 is rejected. Ha is accepted because the t-test < 0.05, namely 0.000 < 0.05 and tcount > ttable, namely 6.362 > 1.701. Although the results of the analysis of the difference in pretest and posttest scores obtained a t-count of 5.682 with a significance level of 0.000. Even though ttable is 1.701 with a significance level of 0.000. With this, it was concluded that H0 was rejected and Ha was accepted because the t-test < 0.05, namely 0.000 < 0.05 and tcount > ttable, namely 5.682 > 1.701. Thus, it is concluded that the Problem-Based Learning model assisted by Mind Mapping in Grade IV at SDN Kalibanteng Kidul 01, Semarang City, has a significant impact on improving students' learning outcomes in Social Studies compared to the control class